2011
DOI: 10.1007/s11162-011-9227-2
|View full text |Cite
|
Sign up to set email alerts
|

Disciplinary Categories, Majors, and Undergraduate Academic Experiences: Rethinking Bok’s “Underachieving Colleges” Thesis

Abstract: Using data from the 2008 University of California Undergraduate Experience Survey, we show that study time and academic conscientiousness were lower among students in humanities and social science majors than among students in science and engineering majors. Analytical and critical thinking experiences were no more evident among humanities and social sciences majors than among science and engineering majors. All three academically beneficial experiences were, however, strongly related to participation in class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 37 publications
2
23
0
1
Order By: Relevance
“…There is substantial evidence that attending a higher-quality or higher-resource school leads to 30 Several other papers have similar findings using a broad set of bans (Backes 2012) a higher likelihood of graduating. Clearly, a first-order concern when undertaking such an analysis is to account for the fact that students with better pre-collegiate academic training are more likely to sort into these schools.…”
Section: Graduationmentioning
confidence: 82%
See 1 more Smart Citation
“…There is substantial evidence that attending a higher-quality or higher-resource school leads to 30 Several other papers have similar findings using a broad set of bans (Backes 2012) a higher likelihood of graduating. Clearly, a first-order concern when undertaking such an analysis is to account for the fact that students with better pre-collegiate academic training are more likely to sort into these schools.…”
Section: Graduationmentioning
confidence: 82%
“…These findings suggest that students do not re-sort in such a way that college quality is kept constant when affirmative action in public colleges and universities is banned. 30 Furthermore, research on enrollment responses to affirmative action bans shows that most of the enrollment effect came from changes in admissions behavior, rather than changes in application patterns among minority students (Card and Krueger, 2005; Antonovics and Backes, 2013). Taken together, these findings suggest that affirmative action bans bind, substantially reducing minority representation at elite public universities in the affected states.…”
Section: Enrollment Effectsmentioning
confidence: 99%
“…In some works important for this paper the research conduct of students reveals confirmed within long-term experience (Brophy, 1986). In another series of works of Brint, Cantwell & Saxena (2012) were discussed modern achievements of research made by students of humanities and social professions in comparison with the achievements of students in the sciences. A special place is occupied by instructional materials as mentioned in works of Cobb, Zhao & Dean (2009) revealing the evidence-based strategies for improving student performance (Schraw, Crippen & Hartley, 2006).…”
Section: Literatures Reviewingmentioning
confidence: 88%
“…In fact, a debate focused on which academic major is known for having the best critical thinkers may be a one-dimensional debate. According to Brint et al (2012), what may originate, or exacerbate, the hypothesized gap between students from different academic majors concerning the quality of their CT skills is, not so much the academic field they are enrolled in, but mostly the teaching approaches to which they are exposed in that academic major. These authors suggest that there are a few variables that make a difference.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors claim that cognitive skills develop differently according to academic major (Kim & Sax, 2011); others state that what is determinant for the development of CT is the teacher's approach (Brint, Cantwell, & Saxena, 2012), or well-structured classroom instruction that fosters a more active, participative, and reflexive approach to learning from students (Pascarella, Wang, Trolian, & Blaich, 2013). As for the association between CT and gender, CT may not be directly dependent on gender , perhaps due to its strong situational nature, making it influenced by, and adapted to, contextual settings.…”
Section: Critical Thinking and Real-world Outcomesmentioning
confidence: 99%